Evolución del arsenal científico para la vigilancia de la capa de ozono (2009)
Among the aims of this work it is included the description of the domains involved in resent scientific papers related with the treatment and the analysis of the ozone layer and with the solar ultraviolet radiation levels (SUVRL). Furthermore, it’s emphasized the more important developed strategies to face the analysis and monitoring of the ozone layer; also, Finding the trends in the scientific community association in order to do research into ozone layer. Finally, it’s suggested a domain in which Andian countries can construct scientific community for tracking the SUVRL on terrestrial surface. Methodologically, it’s searched the trace of the historical scientific criteria which defined the tools and theoretical advance in the present scientific development. It’s found that after more than thirty five years, since the global problem announcement, it has been organized a very wide and strong international scientific community with which efforts pointed out and gear up governments and international organizations in order to control anthropogenic substances that emitted to the atmosphere hurt the ozone layer. It has been achieved successfully to reduce emissions of “fist generation substances" in more than 95 %, but since the major part of them will stay in the atmosphere for at least 40 or 50 years, it is necessary to continue with the efforts to enhance the current methods of control and measurement and to develop new precise and economical methods.